Evaluation of SDHB, SDHD and VHL gene susceptibility testing in the assessment of individuals with non‐syndromic phaeochromocytoma, paraganglioma and head and neck paraganglioma. (6th April 2013) - Jafri, Mariam; Whitworth, James; Rattenberry, Eleanor; Vialard, Lindsey; Kilby, Gail; Kumar, Ajith V.; Izatt, Louise; Lalloo, Fiona; Brennan, Paul; Cook, Jackie; Morrison, Patrick J.; Canham, Natalie; et al.
Summary Objectives Research studies have reported that about a third of individuals with phaeochromocytoma/paraganglioma (PPGL) have an inherited predisposition, although the frequency of specific mutations can vary between populations. We evaluated VHL, SDHB and SDHD mutation testing in cohorts of patients with non‐syndromic PPGL and head and neck paraganglioma (HNPGL). Design Prospective, observational evaluation of NHS practice. Patients Individuals with PPGL/HNPGL referred to a supraregional genetics testing service over a 10‐year period. Measurements Clinical (age, tumour site, malignancy, etc.), mutation frequencies and characteristics. Results A total of 501 probands with PPGL (n = 413) or HNPGL (n = 88) were studied. Thirty‐one percent of patients with PPGL presented had a pathogenic mutation in SDHB, SDHD or VHL. Mutation detection rates were highest in those with a positive family history (62%), malignancy (53%), multiple tumours (33%) or PGL (44%). Twenty‐eight percent of individuals with a single sporadic phaeochromocytoma had a mutation. Overall, 63% of patients with HNPGL had a mutation (92% of those with a family history, 89% of those with multicentric tumours and 34% of those with a single sporadic HNPGL). Penetrance was calculated in 121 SDHB mutation‐positive probands and 187 of their mutation‐positive relatives. Most relatives were asymptomatic and lifetime penetrance in non‐proband SDHB mutation carriers was <50%. Conclusions Practice‐based evaluations of genetic testing in PPGL reveal high mutation detection rates. Although clinical criteria can be used to prioritize mutation testing, mutations were detected in 'low risk groups' indicating a need for comprehensive and inexpensive genetic testing strategies for PPGL and HNPGL.